DETERMINAN ANEMIA PADA IBU HAMIL TRIMESTER III DI PUSKESMAS TEGALREJO YOGYAKARTA TAHUN 2021 - Utari, Dyah Ayu; Hidayat, Asri; Askuri, Askuri (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2023)
Background: Bleeding ranks highest as a cause of maternal death throughout the period. One of the causes of bleeding is caused by low hemoglobin levels in pregnant women which will cause anemia. Objective: to develop an analysis of the factors that influence anemia in pregnant women so as to reduce morbidity and mortality. Method: Quantitative study with a cross-sectional approach. Total sampling data collection technique, collecting data that meets predetermined criteria as many as 287 third trimester pregnant women. Instruments, cohort of pregnant women. Analysis of two variables using the Chi-Square test and multivariate analysis used is logistic regression. Results: Of the 287 respondents, 154 were anemic (53.7%) and 133 were pregnant women who were not anemic (46.3%). Obtained a substantial relationship between maternal age, gestational age, parity, gestational spacing, nutritional status and ANC visits with anemia p-value <0.05, nutritional status shows the most influential determinant of anemia. Pregnant women with at-risk nutritional status are at risk of experiencing anemia 10.187 times higher than those with nutritional status who are not at risk. Conclusion: The determinants of anemia in third trimester pregnant women are mother's age, gestational age, parity, pregnancy interval, nutritional status and ANC visits. Mothers with anemia (53.7%) were 154 and those who were not anemic (46.3%) were 133 pregnant women. The most influential determinant is nutritional status. Suggestion: Improving ANC nutrition counseling services and checking hemoglobin levels to prevent anemia.